RASGRP2 Suppresses Apoptosis via Inhibition of ROS Production in Vascular Endothelial Cells - Takuma Sato; Jun-ichi Takino; Kentaro Nagamine; Kazuto Nishio; Takamitsu Hori (The Scientific World Journal)
We have identified ras guanyl releasing protein 2 (rasgrp2) as a blood vessel related gene from Xenopus embryo. In addition, we reported that RASGRP2 is also expressed in human umbilical vein endothelial cells (HUVEC). It is known that RASGRP2 activates Ras-related protein 1 (Rap1). However, the function of RASGRP2 in human vascular endothelium remains unknown. Therefore, we performed functional analysis of RASGRP2 using immortalized HUVEC (TERT HUVEC). We established a stable RASGRP2 overexpressing cell line (TERT HUVEC R) and mock cell line (mock). Furthermore, we compared the activity of Rap1 and the generation of intracellular reactive oxygen species (ROS), which is related to cell death, in both cell lines. Significant increase in Rap1 activity was observed in the TERT HUVEC R compared to the mock. Furthermore, apoptosis by tumor necrosis factor-α (TNF-α) stimulation was significantly more reduced in the TERT HUVEC R than in the mock. In the mock, apoptosis induced by TNF-α stimulation was decreased by pretreatment with diphenyleneiodonium (DPI), which is an inhibitor of NADPH oxidase (NOX). However, in the TERT HUVEC R, apoptosis induced by TNF-α stimulation was not reduced after pretreatment of DPI. Furthermore, there was no reduction in ROS production in the TERT HUVEC R after DPI pretreatment. In addition, the difference in the degree of apoptosis induced by TNF-α stimulation in both cell lines was consistent with the difference in ROS production in the cell lines. From these results, it was suggested that RASGRP2 activates Rap1 and the activated Rap1 suppresses apoptosis via NOX inhibition.